PELATIHAN MANAJEMEN PADA KOPERASI MAKMUR SEJAHTERA KELURAHAN TITIWUNGEN SELATAN KECAMATAN SARIO KOTA MANADO - Sam J R Saroinsong (ABDIMAS: JURNAL PENGABDIAN KEPADA MASYARAKAT, 2017)
Today the government is aggressively implementing and meningkatkanpembangunan, both material and spiritual development. One area that is being promoted is the business world in order to reduce the number of unemployment in Indonesia is increasing every year.In the business world as well as in the field of cooperative development with all its activities, whether business, skills and awareness activities as well as awareness of cooperatives. All formal and informal organization requires management functions. Because without good management, the organization's goals will not be achieved in an efficient training of cooperative management is essential in the construction and development of cooperatives, including cooperatives prosperous located in the Village Titiwungen Southern District Sario Manado because the success or failure of cooperation depends on the level of knowledge andskills of managers and members of the cooperative, Therefore, training is needed to provide adequate supplies to the board and members, in order to play an active and dynamic for the progress of the cooperative. This devotion activity aims to provide the knowledge of the management of cooperatives to cooperatives to run well and a sustainable for the common welfare. The method used in this devotion is the lesson in class methods (lectures, conferences, case studies, games, program instructions,brainstroming). The results obtained in this training, namely management and members of the Village Cooperative MakmurSejahtera South Titiwungen District of Sario Manado City has knowledge of cooperative management.